Quality control procedure for statutory financial audit : an empirical study - Saha, Siddhartha Sankar; Roy, Mitrendu Narayan (Emerald Publishing Limited, 2017)
Quality Control Procedure for Statutory Financial Audit: An Empirical Study takes a comprehensive look at the quality control framework for statutory financial audit. The authors, Saha and Roy, begin with a conceptual discussion on the quality of statutory audit of financial statements, focusing on identifying the different factors governing quality of audit, and establishing a comprehensive framework for quality control. They delve into the quality control framework in three specific countries: USA, UK and India, based on select parameters, and a comparative study is made among them. Lastly, the authors examine the effectiveness of the existing standards and other legal and regulatory requirements in enforcing quality control policies and procedures and suggesting modifications in those regulations which have been made based on a few respondents' perceptions. Their recommendations can improve the future audit environment in safeguarding stakeholders' interest.